A Critical Analysis of the Book” Ambiguity Function in the Process of Reading a Text” - Maryam Raminnia (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The main aim of the book “Ambiguity function in the process of reading the text authored by Forough Sahba” is to examine complexities discursivities, and narrative techniques making the stories ambiguous. Although the author attempts to present a host of evidence on ambiguous-making techniques for modern stories, there still exist some criticisms on the structure and content of the book which requires its examination more closely.  Disorganization and weakness in the classification of the book’s contents besides misreading of “ambiguity” are the main drawbacks of the present book. More evidently, reducing the ambiguity in stories, merely modern and postmodern ones, equaling the ambiguity with its complexities and discursivities, and also downgrading the ambiguity which are perceived as strategies for maintaining the author’s authority, are the main motives for writing this paper.